Effectiveness of Bamboo Stick Liquid Smoke (Bamboo sp.) With Methanol Extract of Sengon Twig Wood (Falcataria moluccana) as a Disinfectant - Nabillah, Hurient Sani; Sonya, Luluil Fajry Thasya; Fitriani, Dilla Saphira; Muzjahidah, Nelly Siti; Vaolina, Putri; Fadhila, Feldha; Rumidatul, Alfi; Mayuri, Nindya Sekar (Jurnal Riset Kesehatan, 2024)
Pathogenic microorganisms that cause infectious diseases are widely spread in the environment, especially in public places that allow microorganisms to multiply. Disinfectants are used to prevent the spread of these microorganisms. The use of chemical-based disinfectants can cause side effects, so it is necessary to look for alternatives from natural materials, such as a mixture of bamboo stem liquid smoke and methanol extract from Sengon twig wood. The purpose of this study was to determine the effectiveness of a mixture of bamboo stem liquid smoke and methanol extract of Sengon twig on bacteria and fungi. This research method began with an inhibition test of the disc and well diffusion method with five comparison treatments (50:50, 40:60, 30:70, 20:80, 10:90) to obtain the most effective comparison of the volume of 100% bamboo stem liquid smoke mixture and 11% sengon twig wood methanol extract, then tested using the Total Plate Count (TPC) method with swab samples on wooden tables. The results showed that the most effective comparison of the volume of 100% bamboo stem liquid smoke mixture and 11% sengon twig wood methanol extract was the volume ratio of 50:50 from the results of the inhibition zone on Salmonella typhimurium with a diameter of 10.3 mm. The results of the mixed effectiveness test with a ratio of 50:50 with the swab test on the table showed a decrease in the number of bacteria (51%) and fungi (65%). This shows that the mixture of bamboo stem liquid smoke and methanol extract of Sengon twig wood is effective as a disinfectant.